Analisis Implementasi Peraturan Baznas Nomor 2 Tahun 2016 tentang Pembentukan dan Tata Kerja Unit Pengumpul Zakat (UPZ) di UPZ Kecamatan Cibugel Kabupaten Sumedang - Yogi Indrayadi; Encep Abdul Rojak (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The government established a regulations that can be a protection for the implementation of zakat in Indonesia, one of which is PERBAZNAS No. 2 of 2016 concerning the Establishment and Work Procedure of the Zakat Collecting Unit (UPZ). Based on observations in practice, UPZ Cibugel District does not fully implement the regulations contained in PERBAZNAS No. 2 of 2016 as a whole. The purpose of this study is to discuss how to analyze the implementation of PERBAZNAS No. 2 of 2016 in UPZ Cibugel District, both in terms of legality formation and working mechanisms. The method used in this research is empirical-normative juridical with the qualitative approach and sourced from the result of interviews with the head of UPZ Cibugel District and literature studies. The results of this study are: The mechanism for the formation and work of UPZ is regulated in detail in PERBAZNAS No. 2 of 2016, The practice of forming and working UPZ in Cibugel District is officially formed by BAZNAS and its work procedure is assisted by village amilin who do not have a BAZNAS decree, implementation of PERBAZNAS No. 2 In 2016 in the UPZ of Cibugel District there were those that were appropriate and some were not as stated in PERBAZNAS No. 2 of 2016. Abstrak. Pemerintah membentuk regulasi yang dapat menjadi payung bagi pelaksanaan zakat di Indonesia yaitu salah satunya PERBAZNAS No 2 Tahun 2016 tentang Pembentukan dan Tata Kerja Unit Pengumpul Zakat (UPZ). Berdasarkan observasi, pada praktiknya, UPZ Kecamatan Cibugel tidak sepenuhnya menjalankan peraturan yang terdapat dalam PERBAZNAS No 2 Tahun 2016 secara menyeluruh. Tujuan penelitian ini untuk membahas bagaimana analisis implementasi PERBAZNAS No 2 Tahun 2016 di UPZ Kecamatan Cibugel baik dari segi pembentukan legalitas maupun mekanisme kerja. Metode yang digunakan pada penelitian ini adalah yuridis empiris-normatif dengan pendekatan kualitatif dan bersumber dari hasil wawancara ketua UPZ Kecamatan Cibugel dan studi pustaka. Hasil penelitian ini ialah: Mekanisme pembentukan dan kerja UPZ diatur secara rinci pada PERBAZNAS No 2 Tahun 2016, Praktik pembentukan dan tata kerja UPZ Kecamatan Cibugel ialah resmi dibentuk oleh BAZNAS dan tata kerjanya dibantu oleh amilin desa yang tidak memiliki SK BAZNAS, implementasi PERBAZNAS No 2 Tahun 2016 di UPZ Kecamatan Cibugel ada yang sudah sesuai dan ada yang belum sesuai dengan yang tertera pada PERBAZNAS No 2 Tahun 2016.